Dampak eksternalitas ekonomi konversi mangrove menjadi lahan tambak di Kecamatan Samaturu Kabupaten Kolaka - Wahwudi, Bima Dwiki; Nurdiana A; Riani, Irdam; Rosmawati; Sidiq, Azwar (Universitas Halu Oleo, 2024)
The purpose of the study was to indentify Impact of Economic Externalities Mangrove Conversion into Ponds. The study was carried out from January to February 2021 in Sub-district of Latuo, Meura, and Malaha, Samaturu Regency, Kolaka. The samples of study was 15 respondents. Purposive sampling method was used using observation method, interview and documentation. The results of the study indicate that the positive impact includes the revenue of business owner around the ponds area after development has increased with a total value Rp11.800.000/month. While the revenue of fisherman who make use of mangrove ecosystem (such as mud crab, fish, shells, mangrove wood) has decreased with a total value Rp38.100.000/month.